Home-to- School Connection: Literacy Practices of a Teenager Living in Tourist Area - Faizatul Husna; Ida Muliawati; Surya Asra (Universitas Teuku Umar, 2020)
The view of literacy as a social practice has changed the view of researchers to study not only the activities in formal setting but also beyond the school walls (Hull and Schultz, 2002; Street, 2003). This paper aims to shed light how foreign literacy practices in out-of-school context, particularly in tourist areas, may potentially contribute to the students’ literacy ability in the formal context. This ethnographic research was conducted over a two-week period which situated in tourist destination areas, namely Gapang, in the municipality of Sabang, Indonesia. The input data comes mainly from participant observation, audio recordings, interviews and field notes to examine the linkages between outside literacy and school attainment. The findings suggest that there was a linkage between the literacy practices outside and inside school for participant. Eventually, this study will be a beneficial input for teachers, parents and researchers, in the future study, to take into account the learning experiences available in both settings and integrate them into fruitful literacy learning at school.